Handbook of research on contemporary consumerism - Kaufmann, Hans Ruediger, 1958- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2020)
Societal marketing has gained widespread recognition in the marketing discipline both in academia and the professional industry. The Handbook of Research on Contemporary Consumerism is an essential reference source that provides an in-depth understanding on the various aspects and issues of consumerism and reveals the critical success factors and conceptual and theoretical frameworks of these concepts from recent contexts and perspectives. Additionally, it examines the impact of identity on marketing and branding from the consumerist perspective, discusses consumerism as a source of innovation.